In Vitro and In Vivo Activities of Tea Catechins against Helicobacter pylori - Mabe, Katsuhiro (American Society for Microbiology, 1999)
The catechin epigallocatechin gallate showed the strongest activity of the six tea catechins tested against Helicobacter pylori (MIC for 50% of the strains tested, 8 μg/ml). It had bactericidal activity at pH 7 but not at pH ≤5.0. In infected Mongolian gerbils, H. pylori was eradicated in 10 to 36% of the catechin-treated animals, with significant decreases in mucosal hemorrhage and erosion. Tea catechins, therefore, may have therapeutic effects on H. pylori infection.